Implementasi Kurikulum Merdeka dalam Pembelajaran PAI di MI Qita - Ana Faidatul Ummah; Manarul Alam Al Farizi; Fa’izah Darotul Zuhro; Nur Ali; Mohammad Asrori (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: This study aims to analyze the implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) subjects at Madrasah Ibtidaiyah QITA, Malang City, covering aspects of understanding, implementation, impact, challenges, and solutions. The study is grounded in the urgency of integrating the Merdeka Curriculum as an educational reform that promotes value-oriented learning, student autonomy, and the strengthening of students’ religious character. A descriptive qualitative approach was employed using an educational policy case study design. The participants consisted of the school principal, one Islamic education teacher, and four students selected purposively. Data were collected through in-depth interviews, participatory observation, and document analysis, and validated through triangulation of sources and methods to ensure data credibility. The findings reveal that the principal and teachers demonstrated comprehensive understanding and strong commitment to the principles of the Merdeka Curriculum, fostering innovation in value-based Islamic learning. Curriculum implementation emphasized reflective, collaborative, and contextual learning activities that strengthened students’ spirituality and independence. The curriculum’s impact was evident in the improvement of students’ cognitive, affective, and psychomotor abilities, as well as teachers’ professional competence in adaptive instruction. The main obstacles identified were limitations in human resources, facilities, and authentic assessment practices, yet these were mitigated through continuous training, academic supervision, and external partnerships. Overall, the implementation of the Merdeka Curriculum at MI QITA has proven effective, contextually relevant to Islamic values, and serves as a model for developing innovative and sustainable Islamic education policy. Keywords: Merdeka Curriculum; Islamic Religious Education; Policy Implementation; Religious Character. Abstrak: Penelitian ini bertujuan untuk menganalisis secara mendalam implementasi Kurikulum Merdeka pada mata pelajaran Pendidikan Agama Islam (PAI) di Madrasah Ibtidaiyah QITA Kota Malang, yang meliputi aspek pemahaman, pelaksanaan, dampak, hambatan, dan solusi pelaksanaan kebijakan. Latar belakang penelitian ini didasari oleh urgensi penerapan Kurikulum Merdeka dalam membangun paradigma pembelajaran yang berorientasi pada nilai, kemandirian, dan penguatan karakter religius peserta didik. Penelitian menggunakan pendekatan kualitatif deskriptif dengan desain studi kasus kebijakan pendidikan. Subjek penelitian terdiri atas kepala madrasah, satu guru PAI, dan empat peserta didik yang dipilih secara purposif. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen pembelajaran, kemudian divalidasi menggunakan teknik triangulasi sumber dan metode untuk memastikan keabsahan data. Hasil penelitian menunjukkan bahwa pemahaman kepala madrasah dan guru terhadap Kurikulum Merdeka telah berkembang menjadi kesadaran kolektif yang mendorong inovasi pembelajaran berbasis nilai Islam. Pelaksanaan kurikulum berfokus pada aktivitas reflektif, kolaboratif, dan kontekstual yang memperkuat spiritualitas serta kemandirian peserta didik. Dampak penerapan kurikulum terlihat dari peningkatan aspek kognitif, afektif, dan psikomotorik siswa serta profesionalisme guru dalam merancang pembelajaran adaptif. Hambatan utama meliputi keterbatasan sumber daya manusia, sarana, dan asesmen autentik, namun berhasil diatasi melalui pelatihan, supervisi akademik, dan kemitraan eksternal. Secara keseluruhan, implementasi Kurikulum Merdeka di MI QITA berlangsung efektif, relevan dengan nilai-nilai Islam, dan dapat menjadi model pengembangan kebijakan pendidikan Islam yang inovatif dan berkelanjutan. Kata kunci: Kurikulum Merdeka; Pendidikan Agama Islam; Implementasi Kebijakan; Karakter Religius.